Cross-sectional study of the health of southern African truck drivers - Kerstin Klipstein-Grobusch; Samanta Tresha Lalla-Edward; Alex Emilio Fischer; W D Francois Venter; Karine Scheuermaier; Ruchika Meel; Catherine Hankins; Gabriela Gomez; Melvin Draaijer; Alinda G Vos (BMJ Open)
Objectives Lifestyle and working conditions of truck drivers predisposes them to risk-factors associated with communicable and non-communicable diseases, but little is known about the health status of African truck driver. This study aims to assess a cross-section of truckers in South Africa to describe their health information.Setting The study took place across three truck-stop rest areas in the South African provinces of Free State and Gauteng.Participants Eligibility criteria included being males aged 18 years and older, full-time employment as a long-distance truck driver. A total of 614 male truck drivers participated; 384 (63%) were Zimbabwean and 325 (55%) completed high-school.Primary and secondary outcome measures The trucker survey explored demographics; working conditions; sexual, eating and sleeping behaviours; mental health status, medical history and cardiac risk-factors. Medical assessments included physical measurements, glucose and lipid measurements, ECG, carotid intima-media thickness (CIMT) and cardiac ultrasound.Results In the previous month, 554 (91%) participants were sexually active; 522 (86%) had sex with a regular partner; 174 (27%) with a casual partner; 87 (14%) with a sex worker. Average time driving was 10 hours/day, 20 days/month, 302 (50%) never worked night shifts and 74 (12%) worked nights approximately four times per week. 112 (18%) experienced daytime sleepiness and 59 (10%) were ever hospitalised from an accident. Forty-seven (8%, 95% CI 5.3 to 9.5) were HIV-positive, with half taking antiretrovirals. Forty-eight (8%) truckers had some moderate depression, while 21 (4%) suffered from post-traumatic stress disorder. Reported tuberculosis, myocardial infarction, and diabetes were <3%. Prominent cardiac risk-factors included smoking (n=63, 11%), consuming alcohol (>15 drinks/week) (n=54, 9%), overweight/obesity (n=417, 69%), and hypertension (n=220, 36%,95% CI 32.1 to 39.7). ECG results showed 23 (4.9%) and 29 (5.3%) drivers had left ventricular hypertrophy using the Cornell criterion and product, respectively. CIMT measurements indicated nine (4.2%) drivers had a carotid atherosclerotic plaque.Conclusion This first holistic assessment of health among southern African male truck drivers demonstrates substantial addressable cardiovascular risk factors, mental health issues and sexual risk behaviours.